2020
DOI: 10.3390/antiox9040357
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Enhances Palladium-Nanoparticle-Induced Cytotoxicity and Apoptosis in Human Lung Epithelial Adenocarcinoma Cells A549 and H1229

Abstract: Palladium nanoparticles (PdNPs) are increasingly being used in medical and biological applications due to their unique physical and chemical properties. Recent evidence suggests that these nanoparticles can act as both a pro-oxidant and as an antioxidant. Melatonin (MLT), which also shows pro- and antioxidant properties, can enhance the efficacy of chemotherapeutic agents when combined with anticancer drugs. Nevertheless, studies regarding the molecular mechanisms underlying the anticancer effects of PdNPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 113 publications
1
38
0
Order By: Relevance
“…Purification and characterization were carried out according to a previously described method. 38 Detailed methodology given as Supplementary File .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purification and characterization were carried out according to a previously described method. 38 Detailed methodology given as Supplementary File .…”
Section: Methodsmentioning
confidence: 99%
“… 40 , 42 Lipid hydroperoxide and 8-isoprostane levels were also measured as previously described. 38 , 43 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination effect increased mitochondria-mediated stress and apoptosis, which was confirmed by the increased expression levels of apoptotic genes. 42 The antiproliferative and antitumor effects of MLT were investigated in B16-F10 cell murine melanoma models. MLT reduced the growth rate and migration of B16-F10 cells, induced G2/M cell cycle arrest, and altered cytoskeletal organization.…”
Section: Role and Therapeutic Potential Of Mlt In Lung Cancermentioning
confidence: 99%
“… 45 MLT directly reduces osteoclast differentiation, bone resorption activity and promotes apoptosis of mature osteoclasts and also MLT inhibits RANKL production in lung and prostate cancer cells by downregulating the p38 MAPK pathway 46 Recently, we have shown that combination of MLT and retinoic acid induced cytotoxicity and apoptosis in human lung epithelial adenocarcinoma cells A549 and H1229 by enhancing oxidative stress and decreasing mitochondrial dysfunctions. 42
Figure 3 Tumor suppressive properties of MLT on lung cancer by targeting family of transcription factors.
…”
Section: Role and Therapeutic Potential Of Mlt In Lung Cancermentioning
confidence: 99%